Cervicovaginal loads of Gardnerella spp. are increased in immunocompetent women with persistent high-risk human papillomavirus infection - Belleti, Rafael [UNESP] (2022)
Introduction. Two high-oncogenic-risk human papilomavirus (hrHPV) genotypes - HPV16 and HPV18 - cause most of the cases of cervical cancer worldwide. Bacterial vaginosis is associated with increased hrHPV persistence, although the mechanism underlying this association remains unclear. Gardnerella spp. are detected in nearly all cases of bacterial vaginosis and are the major source of cervicovaginal sialidases. The NanH1 gene is present in virtually all Gardnerella sialidase-producing strains and has been proposed as a potential marker for persistent hrHPV infection.Hypothesis.Gardnerella spp. load and the NanH1 gene are associated with hrHPV persistence.Aim. To compare the cervicovaginal load of Gardnerella spp. and the frequency of the NanH1 gene between women with persistent HPV16 and/or HPV18 infection and those who cleared the infection after 11 months.Methodology. Among a population of 1638 HPV screened, we detected 104 with positive HPV16 and/or HPV18 results. Samples were obtained at two time points (baseline and at a median of 11 months at follow-up) and tested using the Linear Array HPV Genotyping kit (Roche Molecular Systems, Pleasanton, CA, USA). Based on their HPV16/HPV18 status at enrolment and follow-up, participants were assigned to 'persistence' or 'clearance' groups. We used cervicovaginal fluid samples obtained upon enrolment to determine the load of the 23 s rRNA gene of Gardnerella spp. and the presence of the NanH1 gene using real-time polymerase chain reaction (PCR). We compared Gardnerella spp. loads and NanH1 frequency between the groups by, respectively, Mann-Whitney and chi-squared tests, with a P-value <0.05 considered to be significant.Results. Of the 104 participants who were positive for HPV16/HPV18, 73 (70.2 %) persisted with at least 1 of the baseline genotypes at follow-up, while 31 (29.8 %) cleared the infection in this time frame. Participants in the persistence group had significantly higher loads of Gardnerella spp. [5.8E+02 (0-3.0E+05) copies µl-1] than those in the clearance group [9.9E+01 (0-7.7E+04) copies µl-1] (P=0.03). The baseline frequency of NanH1 was higher in the persistence' (n=46, 63.0 %) than in the clearance (n=14, 45.2 %) group, although this was not statistically significant (P=0.09).Conclusion. These findings reinforce the negative effect of vaginal microbiota for the clearance of hrHPV and indicate a possible association between sialidase-producing species with hrHPV persistence.